واقع تدفقات الاستثمار الأجنبي المباشر الى الجزائر في ظل أزمتي كورونا والنفط - طلحي, فاطمة الزهراء (جامعة الوادي - University of Eloued, 2022)
قطعت الجزائر اشواطا مهمة في تحسين مناخها الاستثماري لاستقطاب الاستثمارات الأجنبية المباشرة، وذلك في ظل الامكانيات والمقومات التي تتوافر عليها ،إلا أن دخول الاستثمارات الأجنبية المباشرة للجزائر لا يعكس ما هو مطلوب من وراء تحسين المناخ الاستثماري ،لذلك تهدف هذه الورقة البحثية الى ابراز مستوى وحجم تدفقات هذه الاستثمارات من خلال دراسة وتحليل واقع المناخ الاستثماري ومدى تأثير ازمتي كورونا والنفط على أداء بعض المؤشرات المختارة و المعتمدة في تقييم المناخ الاستثماري بالجزائر منها ما هو الكمي (تطور أداء المؤشر الاقتصادي العام)، و ما هو نوعي (مؤشر الحرية الاقتصادية، ومؤشر التنافسية العالمي) ،حيث تبين ان ترتيب الجزائر بقي متأخرا مقارنة بالدول العربية، بالرغم من عديد القرارات الاستثمارية الحمائية المتخذة للتصدي لتحالف الازمتين انخفاض أسعار البترول المتواصل و كوفيد 19 Algeria has made important compulsions in improving its investment climate to attract foreign direct investment, under the possibilities and interests that are available, but the entry of foreign direct investment for Algeria does not reflect what is required from improving investment climate, so this research paper is required to highlight the level and size of flows These investments are by studying and analyzing the reality of investment climate and the impact of my Corona crisis and oil to perform some selected indicators and adopted in an investment climate assessment in Algeria, of which is quantity (develop the performance of the général economic index), and what is the quality (Economic Freedom Index) and the World Competitor Index Where Algeria's arrangement remained late compared to Arab countries, despite the many protectionist investment decisions to address the crisis alliance, low oil prices and covid 19
The reality of foreign direct investment flows to Algeria in light of the Corona and oil crises
مقال
Keywords: الاستثمار الاجنبي المباشر؛ المناخ الاستثماري، المؤشرات الاقتصادية، الجزائر، كورنا؛ النفط.; FDI; investment climate, economic indicators, Algeria, corona; oil